2021
DOI: 10.2139/ssrn.3765293
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Cash Transfers and Shocks: Evidence from the Philippines

Abstract: We evaluate the impact of the Pantawid Pamilyang Pilipino Program, a conditional cash transfer (CCT) program in the Philippines, on household welfare in the presence of various shocks to household members such as death, illness, loss of employment, business failure, and natural or man-made disasters. Using a regression discontinuity design (RDD), we estimate whether the CCT program induces its beneficiary households to adjust their spending patterns differently from nonbeneficiaries when exposed to shocks. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
3
1
Order By: Relevance
“…This result could be due to the fact that low-income households are looking for in-kind benefits that could be useful for them to meet their daily ends. These results do not support the fact that low income households could use cash to spend in risky consumption (like alcohol and cigarettes) as is shown in some of the previous studies [ 18 , 19 ].…”
Section: Data and Resultscontrasting
confidence: 78%
“…This result could be due to the fact that low-income households are looking for in-kind benefits that could be useful for them to meet their daily ends. These results do not support the fact that low income households could use cash to spend in risky consumption (like alcohol and cigarettes) as is shown in some of the previous studies [ 18 , 19 ].…”
Section: Data and Resultscontrasting
confidence: 78%
“…One randomized control trial (RCT) from the United States found that receipt of an unconditional cash transfer did not increase spending on alcohol, tobacco, or drugs among low-income mothers ( Yoo et al, 2022 ). Other studies support the claim that cash transfers do not increase spending on tempting goods such as alcohol ( Evans & Popova, 2014 ; Flaminiano, 2021 ; Handa et al, 2018 ; Marinescu, 2018 ). However, an analysis of cash assistance programs in Peru did find that the receipt of cash transfers was associated with small increases in spending on alcohol and sugar-sweetened products ( White & Basu, 2016 ).…”
Section: Discussionmentioning
confidence: 92%
“…Costsharing affects more than 40% of patients' families. 1 The economic impact extends further, with patients with cancer and caregivers facing a yearly loss of 1.1 billion Philippine Peso (PHP) ($18.7 million US dollars [USD]) in wages because of foregone work productivity linked to the illness. 4 Psychosocial effects include fear, anxiety, social isolation, and uncertainty about the future.…”
Section: Filipino Family Dynamicsmentioning
confidence: 99%
“…In the Philippines, a large low- and middle-income country (LMIC) of 110 million people, 2022 saw over 110,000 cancer deaths, representing the third leading cause of death in the country. 1-3 Almost 190,000 new diagnoses were reported in 2022, driven by common cancers of the breast, lung, and colorectum. 2 Within Southeast Asia, the Philippines records one of the highest premature cancer-related deaths.…”
Section: Introductionmentioning
confidence: 99%